Higher precision of heart rate compared with VO2 to predict exercise intensity in endurance-trained runners - Reis, V. M.; van den Tillaar, R.; Marques, M. C. (Journal of Sports Science & Medicine, 2011)
The aim of the present study was to assess the precision of oxygen uptake with heart rate regression during track running in highly-trained runners. Twelve national and international level male long-distance road runners (age 30.7 ± 5.5 yrs, height 1.71 ± 0.04 m and mass 61.2 ± 5.8 kg) with a personal best on the half marathon of 62 min 37 s ± 1 min 22 s participated in the study. Each participant performed, in an all-weather synthetic track five, six min bouts at constant velocity with each bout at an increased running velocity. The starting velocity was 3.33 m·s-1 with a 0.56 m·s-1 increase on each subsequent bout. VO2 and heart rate were measured during the runs and blood lactate was assessed immediately after each run. Mean peak VO2 and mean peak heart rate were, respectively, 76.2 ± 9.7 mL·kg-1·min-1 and 181 ± 13 beats·min-1. The linearity of the regressions between heart rate, running velocity and VO2 were all very high (r > 0.99) with small standard errors of regression (i.e. Sy.x < 5% at the velocity associated with the 2 and 4 mmol·L-1 lactate thresholds). The strong relationships between heart rate, running velocity and VO2 found in this study show that, in highly trained runners, it is possible to have heart rate as an accurate indicator of energy demand and of the running speed. Therefore, in this subject cohort it may be unnecessary to use VO2 to track changes in the subjects' running economy during training periods.